Reaching for Independence: Challenges for a New Concept of Wheelchair Design - Medola, Fausto Orsi; Fortulan, Carlos Alberto; Santana, Carla da Silva; Elui, Valeria Meirelles Carril (IntechOpen, 2012)
None